Program development of fatigue life prediction analysis - Kuehsamy, Shemuel Joash (2019)
Fatigue is a serious and dangerous issue that needs to be tackled by engineers. In order to tackle this problem, a prediction of the fatigue crack growth is needed. Thus, the methods to predict the fatigue crack growth is studied as well as the different types of commercial software that can automate the process. These commercial programs are usually expensive and unavailable to students as such this project aims to use the simple Paris Law as a basis to write a program using Matlab that can predict the crack growth in simple plates. The results of the created program are then compared against the results of the demo version of a commercial program which is CrackWise. The simulated results from both programs are also then compared to experimental results as well.